Pricing Sustainable Shipping of Coffee: Consumers' Preferences and Willingness to Pay for Emission Reductions and Offsets - Ulrich Bek (Junior Management Science (JUMS), 2022)
The goal of this study is to explore whether decarbonization of maritime shipping and the full supply chain are valued in customer perception. Understanding consumers' preferences and willingness to pay (WTP) for sustainable maritime shipping of goods can provide opportunities to spread the costs of required sectorial changes. Decarbonization labels were compared to the Fairtrade and European organic label. A discrete choice experiment (DCE) with 299 participants was performed and supporting data was considered for an exhaustive description of preferences and WTP in the exemplary use case of filter coffee. The results indicate a significant WTP premium for all labels. On average, direct reductions of all supply chain emissions were valued at 2.82 exteuro (all values per 500g of coffee) and are thus comparable in importance to the Fairtrade label estimated at 2.77 exteuro. Maritime shipping offsets, reductions and offsets for the full supply chain were valued at average premiums of 1.79 exteuro, 1.95 exteuro and 1.89 exteuro. Organic labelling led to an average premium of 1.61 exteuro. A random parameter logit model with correlated parameters found significant preference heterogeneity across participants for all labels. Participants preferring whole bean to ground coffee did not significantly differ in their underlying preferences for the sustainability dimensions but in their price perception and effectively displayed higher WTP for all attributes. This study contributes to current research by providing a thorough measurement of preferences and WTP for emission reductions along the supply chain and is the first to assess offsets compared to direct reductions in a controlled setting for a common product use case.
Keywords: 650; Sustainable maritime shipping; direct decarbonization; carbon offsets; discrete choice experiment; pricing